Study of Environmental Hygiene of Islamic Boarding Schools in H. Abdullah Alin Sundi hill district, Solok Regency. - Sukir Sukir (International Journal of Educational Dynamics, 2019)
Abstract This study aims to obtain data, process, analyze and discuss the Study of Environmental Hygiene in Islamic Boarding Schools in H. Abdullah Alin Tagak. Viewed from: 1) Attitude, 2) Behavior, 3) Availability of Trash Tubs, 4) Teacher's This type of research belongs to qualitative research. Respondents in this study were in the form of santri and teachers in the Islamic Boarding School environment of H. Abdullah Alin Tagak, Subdistrict, western market district. Informants in this study were taken by purposive sampling. The informants of this study were 25 people. Keywords: Study of Environmental Hygiene in Islamic Boarding Schools